Scan QR code or get instant email to install app

Skip to content
#
Solve the equation: \(12x + 9 = 4x + 7\) =

### Related Information

Question:

`_________`

.
A
\(\frac{{-1} }{{4} }\)

explanation

We need to isolate all terms containing x on one side of the equation. We can eliminate 4x from the right-hand side of 12x + 9 = 4x + 7 by subtracting 4x from both sides of the equation.

12x + 9 = 4x + 7

Subtract 4x from both sides.

12x + 9 -4x = 4x + 7 -4x

8x + 9 = 7

Next, eliminate 9 from the left-hand side of the last equation by subtracting 9 from both sides of the equation.

8x + 9 - 9= 7 - 9

8x = -2

Note how we have isolated all terms containing x on one side of the equation. Finally, to “undo” multiplying by 8, divide both sides of the equation by 8 and reduce to the lowest terms.

\(\frac{\mathrm{8x} }{\mathrm{8}} =\frac{\mathrm{-2} }{\mathrm{8} }\)

\(x=\frac{\mathrm{-1} }{\mathrm{4} }\)

Take more free practice tests for other GED topics with our ged practice test now!

Comments